2018
DOI: 10.1111/hiv.12632
|View full text |Cite
|
Sign up to set email alerts
|

Liver stiffness reduction and serum fibrosis score improvement in HIV/hepatitis C virus‐coinfected patients treated with direct‐acting antivirals

Abstract: A reduction in liver stiffness and an improvement in fibrosis scores were observed in HIV/HCV-coinfected patients soon after DAA treatment. The clinical implications of these observations need to be evaluated in larger populations with longer follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
3
12
1
Order By: Relevance
“…All HIV/HCV coinfected patients achieved SVR at 12 weeks after end of treatment. At this point, liver enzymes returned to normal levels (in all patients in whom levels of liver enzymes were increased at baseline], and the values of the APRI score and the FIB-4 index significantly diminished, in agreement with previous studies [ 41 , 42 ], suggesting a rapid improvement in hepatic injury after HCV eradication. We also observed a reduction of liver stiffness (LS] and all patients presented values < 7.1 KPa after a mean period of 25 months after treatment initiation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…All HIV/HCV coinfected patients achieved SVR at 12 weeks after end of treatment. At this point, liver enzymes returned to normal levels (in all patients in whom levels of liver enzymes were increased at baseline], and the values of the APRI score and the FIB-4 index significantly diminished, in agreement with previous studies [ 41 , 42 ], suggesting a rapid improvement in hepatic injury after HCV eradication. We also observed a reduction of liver stiffness (LS] and all patients presented values < 7.1 KPa after a mean period of 25 months after treatment initiation.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, we could not verify if this decrease in LS values paralleled the rapid decrease of liver enzymes, which would support the link between LS and liver enzymes. Interestingly, other authors have found significant decreases of LS early after HCV eradication with DAAs therapy (12 weeks after end of treatment], in parallel with the normalization of liver enzymes [ 41 , 42 ], which supports an influence of necroinflammatory activity on LS values [ 40 ]. An interesting finding in our study was the significant increase in CD4 counts after HCV eradication in a relatively short period of only 12 weeks after the end of treatment, which supports a negative impact of HCV on immune restoration in HIV patients on ART, as has been previously suggested [ 43 ].…”
Section: Discussionmentioning
confidence: 78%
“…Liver biopsy, the gold standard for assessment of fibrosis and steatosis, has now been replaced by non-invasive methods such as the fibrosis 4 (FIB-4) index for liver fibrosis, the HSI, and VCTE [20][21][22]41]. In addition to biopsy and VCTE, the HSI was used to detect steatosis in this cohort because all of its components were collected as part of routine care.…”
Section: Discussionmentioning
confidence: 99%
“…Liver biopsy is the reference standard for diagnosing hepatic fibrosis and steatosis; however, it is invasive, expensive and affected by biopsy size (sampling error) and interobserver variation among pathologists [20]. Consequently, non-invasive serum-based tests and imaging techniques, such as vibration-controlled transient elastography (VCTE) to measure fibrosis with controlled attenuation parameter (CAP) measurement to assess hepatic steatosis, respectively, have replaced liver biopsy in most centers [21,22]. However, because VCTE with CAP may not be available in many clinical settings, other non-invasive serum-based assessments of steatosis, such as the hepatic steatosis index (HSI) have been developed [23,24] but not assessed in those with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with severe inflammation or liver steatosis at baseline have greater improvements in the APRI index compared to those with lower inflammation and no steatosis (19). In the study conducted by Fabbri et al, APRI decreased in hepatitis C/HIV co-infected patients who underwent treatment with DAAs from a median of 0.94 to 0.37 (20).…”
Section: Aprimentioning
confidence: 95%